Band Structure Engineering of WSe2 Homo‐Junction Interfaces via Thickness Control. Issue 4 (16th December 2021) - Shin, June‐Chul; Kim, Yeon Ho; Watanabe, Kenji; Taniguchi, Takashi; Lee, Chul‐Ho; Lee, Gwan‐Hyoung
Abstract: Transition metal dichalcogenides (TMDs), one of the 2D semiconductors, such as molybdenum disulfide (MoS2 ) and tungsten diselenide (WSe2 ), exhibit novel physical and electronic properties that are useful for electronic and optoelectronic applications. Recently, the van der Waals heterostructures consisting of different 2D materials have been studied actively as various combinations of 2D materials can be fabricated with exceptional performance and physical properties. Nevertheless, study on homo‐junction of the same TMDs layers is lacking. Here, it is demonstrated that a vertical homo‐junction consisting of two WSe2 flakes with different thicknesses shows anti‐ambipolar transport behavior due to a thickness‐induced band offset at the interface. Photo‐response current is generated by tunneling‐mediated interlayer recombination at the WSe2 homo‐junction. The band structures of homo‐junctions of TMDs can be engineered by the thickness, which would be beneficial for understanding transport at the interfaces of 2D materials and developing the next generation devices. Abstract : The vertical homo‐junction consisting of two WSe2 flakes with different thicknesses shows anti‐ambipolar transport behavior due to a thickness‐induced band offset at the interface. The band structures of homo‐junctions of transition metal dichalcogenides can be engineered by the thickness, which would be beneficial for understanding transport at the interfaces of 2D materials and development of next generation devices.